2013
DOI: 10.1093/annonc/mdt502
|View full text |Cite
|
Sign up to set email alerts
|

Formulary availability and regulatory barriers to accessibility of opioids for cancer pain in Latin America and the Caribbean: a report from the Global Opioid Policy Initiative (GOPI)

Abstract: The nations of the Caribbean, Central America and South America form a heterogeneous region with substantial variability in economic, social and palliative care development. Palliative care provision is at varied stages of development throughout the region. The consumption of opioids in Latin America and the Caribbean is variable with moderate levels of consumption by international standards (1-10 mg morphine equivalents/capita/year) observed in Argentine, Brazil, Chile, Colombia, Cuba, Mexico, Costa Rica, Uru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 13 publications
0
38
0
6
Order By: Relevance
“…Four studies reported data from Jamaica [32–35], three each from Barbados [27, 34, 35] and Cuba [2931], two studies each from Trinidad and Tobago [34, 35], St Lucia [34, 35] and Grenada [28, 35] and one study reported from each of the following islands: Antigua and Barbuda, Montserrat, St Kitts and Nevis, St Vincent and the Grenadines [35], Anguilla, Dominica and the Dominican Republic [34] . Please refer to Table 4 to view the studies in detail.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies reported data from Jamaica [32–35], three each from Barbados [27, 34, 35] and Cuba [2931], two studies each from Trinidad and Tobago [34, 35], St Lucia [34, 35] and Grenada [28, 35] and one study reported from each of the following islands: Antigua and Barbuda, Montserrat, St Kitts and Nevis, St Vincent and the Grenadines [35], Anguilla, Dominica and the Dominican Republic [34] . Please refer to Table 4 to view the studies in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies [27, 29–32, 34, 35] used quantitative methodological approaches, and cross sectional survey designs were utilized within these studies. One study used a mixed methods design with qualitative and quantitative components [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may be explained by availability of effective, subsequent lines of therapy, which are probably less extensive in developing compared with developed countries. Furthermore, the overall quality of health care, especially of supportive and palliative therapy, may be lower in developing countries [25,26] and availability of such care has been shown to be associated with improved survival [4]. The increasing toxicity of new anticancer drugs is well established [20] and therefore effective palliative care is especially important as new drugs move from clinical trials to routine practice where their use in less selected patients would probably lead to a less favourable balance between benefit and harm [27].…”
Section: Discussionmentioning
confidence: 99%
“…This massive collaborative project, known as the Global Opioid Pain Initiative (GOPI), and the data derived from it, [17][18][19][20][21][22][23][24] set an international agenda to address problems of access, cost and regulatory barriers around the world, and placed ESMO squarely as a central participant in this critical global endeavour.…”
Section: Improving Access To Carementioning
confidence: 99%